L'importante ruolo degli open data nelle emergenze (GEOmedia, 2016)
The important role of open data in emergencies During emergencies, the geographic information plays a very important and delicate role becoming the main tool to understand what happened and to take decisions. The data therefore will play a crucial role. The availability of data as soon as possible, with the guarantee that they are correct, is a non-trivial aspect.